1978
DOI: 10.1002/ange.19780900208
|View full text |Cite
|
Sign up to set email alerts
|

Die charakteristischen Eigenschaften homoaromatischer Systeme

Abstract: Verbindungen mit homoaromatischen Eigenschaften sind nach wie vor ein auflerordentlich interessantes Gebiet der Chemie. Derzeit wird u. a. versucht, das AusmaR der weitreichenden Delokalisierung von Elektronen experimentell zu bestimmen, die Wechselwirkungen in Molekiilen mit zwei oder mehr isolierenden Atomen zu ermitteln und energetische sowie geometrische Eigenschaften der homoaromatischen Systeme theoretisch abzuschatzen. In diesem Aufsatz werden in erster Linie neuere spektroskopische und strukturelle Bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 176 publications
0
14
0
Order By: Relevance
“…cis,cis,cis-l,5,9-cyclododecatriene was obtained by the method of Untch and Martin," with the following exception: it was found that elimination with potassium r-butoxide in tbutanol gave a faster and cleaner elimination to the tribromocyclododecatrienes in high yield; this was therefore the method of choice for this dehydrobromination. I,2,5,6,9,cis, In a typical experiment, 109 of triene 9 (62 mmol) was dissolved in about 150 mL of CCI. in a 500-mL round-bottom flask.…”
Section: R 1 • R 2-brmentioning
confidence: 99%
See 4 more Smart Citations
“…cis,cis,cis-l,5,9-cyclododecatriene was obtained by the method of Untch and Martin," with the following exception: it was found that elimination with potassium r-butoxide in tbutanol gave a faster and cleaner elimination to the tribromocyclododecatrienes in high yield; this was therefore the method of choice for this dehydrobromination. I,2,5,6,9,cis, In a typical experiment, 109 of triene 9 (62 mmol) was dissolved in about 150 mL of CCI. in a 500-mL round-bottom flask.…”
Section: R 1 • R 2-brmentioning
confidence: 99%
“…The crude material was used without further purification in the next step. Z,Z,5,5, A portion of the crude mixture of hexabromocyclododecanes (6.8 g, 10.6 mmol) was dissolved in dry THF (20 mL) under nitrogen. A solution of sodium ethoxide in ethanol [prepared by adding 0.73 g (31.7 mmol) of sodium to 50 mL of dry EtOH) was added dropwise over about 30 min.…”
Section: R 1 • R 2-brmentioning
confidence: 99%
See 3 more Smart Citations